MULTIFACTOR RESERVOIR LEAKAGE DETECTION, MONITORING, AND MANAGEMENT SYSTEM USING PATTERN RECOGNITION AND ULTRASONIC SENSORS - Adamu, Abubakar (FUDMA Journal of Sciences, 2026)
Reservoir leakage constitutes a crucial challenge to water resource, monitoring, safety, management and environmental sustainability. Late detected or undetected leakage can lead to loss of water, structural degradation, and severe environmental consequences. This paper presents multifactor reservoir leakage detection, monitoring, and management system based on ultrasonic sensors and pattern recognition techniques. The proposed system integrates multiple ultrasonic signal features, including temporal variation, echo amplitude and signal attenuation, alongside environmental compensation factors such as pressure and temperature. A pattern recognition framework is employed to classify reservoir states into normal and severe leakage conditions. Experimental evaluation demonstrates that the proposed system achieves high detection accuracy, reduced false alarm rates, and robust performance under varying noise and operational conditions. The results confirm the feasibility of the system for real-time reservoir monitoring and intelligent leakage management.